2013
DOI: 10.1002/jcph.220
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in pharmacokinetics and pharmacodynamics of zolpidem following sublingual administration

Abstract: The effect of dose and gender on the pharmacokinetics (PK) and pharmacodynamics (PD) of zolpidem after administration of a buffered zolpidem sublingual tablet (ZST; Intermezzo®, Purdue Pharma L.P., Stamford, CT, USA) was evaluated in healthy non-elderly male and female volunteers. Subjects received a single morning dose of ZST (1.0, 1.75, and 3.5 mg) or placebo in a four-way crossover study. In male and female subjects zolpidem PK were linear, with area under the curve (AUC) proportional to dose, and apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 35 publications
4
57
1
1
Order By: Relevance
“…Such similarity in drug exposure of zolpidem had also been reported for the marketed sublingual zolpidem lozenge (Intermezzo) in which the gender difference resulted in gender-specific dose levels for females (1.75 mg) and males (3.5 mg) for safety reason (for example, next-morning residual effect) as recommended by U.S. FDA. 14,15 Similar to the historical clinical data of Intermezzo, [13][14][15] our results of weight-normalized clearance also indicated that male subjects cleared zolpidem from body at a higher rate than female subjects, which warrant further investigation in the following clinical studies.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Such similarity in drug exposure of zolpidem had also been reported for the marketed sublingual zolpidem lozenge (Intermezzo) in which the gender difference resulted in gender-specific dose levels for females (1.75 mg) and males (3.5 mg) for safety reason (for example, next-morning residual effect) as recommended by U.S. FDA. 14,15 Similar to the historical clinical data of Intermezzo, [13][14][15] our results of weight-normalized clearance also indicated that male subjects cleared zolpidem from body at a higher rate than female subjects, which warrant further investigation in the following clinical studies.…”
supporting
confidence: 78%
“…11,13 Since the clearance rate of zolpidem in women is lower than that in men, the dose for Intermezzo recommended by US FDA is 1.75 mg for women and 3.5 mg for men, which is taken only once per night. 11,14,15 The starting dose of ZNS in this dose-escalating clinical study was selected to be 1.75 mg/day since this dose should be safe in humans, based on our non-clinical PK and toxicological studies in dogs and previous human experience at similar or higher dose of zolpidem tartrate administered by oral or intravenous routes. In an acute toxicity and toxicokinetic study, 3 groups of sleep deprived rats received IN doses of ZNS (0.208 mg/rat, 0.416 mg/rat, or 0.832 mg/rat) once daily for 7 consecutive days.…”
Section: Brief Summarymentioning
confidence: 99%
“…1,2 The peak concentration of the sublingual formulation of zolpidem was 45% higher in women than men. 3 Some studies have shown that these pharmacokinetic differences are associated with safety differences. At 5 h post daytime zolpidem administration and testing, poorer automobile driving was found 3 and in the morning 4 h after middle of the night zolpidem administration, poorer automobile driving was shown in women than men.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, experimental studies of sex differences in the pharmacokinetics and pharmacodynamics of zolpidem in human men and women found that body weight, not sex, is the culprit. Women clear zolpidem from their system more slowly than men, but body weight eliminates the statistical significance of sex as a variable in clearance of zolpidem (8). Because body weight, not sex, is the independent biological variable, sex-based preclinical research protocols would likely not have predicted sex differences in rates of ADE with zolpidem.…”
mentioning
confidence: 99%